Developmental exposure to Δ(9)-tetrahydrocannabinol (THC) causes biphasic effects on longevity, inflammation, and reproduction in aged zebrafish (Danio rerio) - Pandelides, Zacharias (GeroScience, 2020)
Increased availability of cannabis and cannabinoid-containing products necessitates the need for an understanding of how these substances influence aging. In this study, zebrafish (Danio rerio) were exposed to different concentrations of THC (0.08, 0.4, 2 μM) during embryonic-larval development and the effects on aging were measured 30 months later and in the offspring of the exposed fish (F1 generation). Exposure to 0.08 μM THC resulted in increased male survival at 30 months of age. As the concentration of THC increased, this protective effect was lost. Treatment with the lowest concentration of THC also significantly increased egg production, while higher concentrations resulted in impaired fecundity. Treatment with the lowest dose of THC significantly reduced wet weight, the incidence of kyphosis, and the expression of several senescence and inflammatory markers (p16(ink4ab), tnfα, il-1β, il-6, pparα and pparγ) in the liver, but not at higher doses indicating a biphasic or hormetic effect. Exposure to THC did not affect the age-related reductions in locomotor behavior. Within the F1 generation, many of these changes were not observed. However, the reduction in fecundity due to THC exposure was worse in the F1 generation because offspring whose parents received high dose of THC were completely unable to reproduce. Together, our results demonstrate that a developmental exposure to THC can cause significant effects on longevity and healthspan of zebrafish in a biphasic manner. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11357-020-00175-3) contains supplementary material, which is available to authorized users.